Barnehager som konkurrerende virksomheter - Hanne Fehn Dahle (Nordic Studies in Education, 2020)
Whenever the amount of placements in kindergarten exceeds the number of children, the various kindergartens are inclined to compete in order to attract the families. Drawing on Freidson’s (2001) theory on professionalism, the present article focuses on the ways in which teachers in kindergarten experience and assess such competition. The empirical data stem from interviews with 18 teachers employed by large enterprises of private kindergartens. The analysis demonstrates that while they identify with the “third logic”, the teachers are faced with a competitive market regulated by supply and demand. Thus, they find themselves caught in the tension between, on one hand, the ethical values inherent to the profession, stressing their own professional judgement and the interests of all the children, and on the other, the owner’s need to win the competition, leading to product orientation, marketing, and secrecy.